The involvement of cytochrome P450 system in the fate of 2,4,6-trinitrotoluene in European eel (Anguilla anguilla) - Della Torre, C.; Corsi, I.; Alcaro, L.; Amato, E.; Focardi, S. (Biochemical Society Transactions, 2006)
TNT (2,4,6-trinitrotoluene) was the most common nitro aromatic explosive available in WorldWar II ammunitions. The presence of ordnance dumped at sea might represent a great concern for marine species living close to dumping sites and the toxicological properties of the chemicals released into the marine environments need to be evaluated. The aim of the present study is to investigate the involvement of CYP (cytochrome P450) system in the metabolism of TNT in marine organisms by using the European eel [Anguilla anguilla (Linnaeus, 1758)] as model species. In vivo exposure to sublethal concentration of TNT (0.5, 1 and 2.5 mg/l) leads to a significant decrease in the phase I CYP1A catalytic activities such as EROD (7-ethoxyresorufin-O-de-ethylase) and MROD (7-methoxyresorufin-O-de-ethylase). On the opposite, a significant increase in NADPH cytochrome c reductase activity aswell as phase II UDP- glucuronosyltransferase activity is observed. An inhibition at enzyme level is hypothesized for both CYP1A enzymes, also confirmed by a similar decrease observed after in vitro exposure. An active role of NADPH cytochrome c reductase and phase II enzymes in the TNT metabolism may also be hypothesized. ©2006 Biochemical Society.